2020
DOI: 10.1177/0300985820948820
|View full text |Cite
|
Sign up to set email alerts
|

Feline Morbillivirus Infection Associated With Tubulointerstitial Nephritis in Black Leopards (Panthera pardus)

Abstract: Feline morbillivirus (FeMV) is an emerging RNA virus in the Paramyxoviridae family that was recently discovered in domestic cats ( Felis catus). To date, 2 genotypes (FeMV-1 and FeMV-2) have been detected in cats from various countries, and FeMV-1 is recognized as a pathogen associated with nephritis. However, information regarding the pathological roles and potential transmission to other felids is limited. In this article, we describe the identification of FeMV in 2 black leopards ( Panthera pardus) in Thail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 35 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…Recently, it was shown that domestic cats of Chile have a high seroprevalence for both FeMV genotypes [29]. As mentioned above, black leopards (Panthera pardus) were also shown to be susceptible to FeMV [38], which further support a hypothesis of possible FeMV infections in guignas. The seroprevalence of FeMV in guignas is in accordance with published results from studies of domestic cats from China [14], the UK [17] and Japan [45], although comparison with these investigations may be difficult due to differences in experimental techniques.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Recently, it was shown that domestic cats of Chile have a high seroprevalence for both FeMV genotypes [29]. As mentioned above, black leopards (Panthera pardus) were also shown to be susceptible to FeMV [38], which further support a hypothesis of possible FeMV infections in guignas. The seroprevalence of FeMV in guignas is in accordance with published results from studies of domestic cats from China [14], the UK [17] and Japan [45], although comparison with these investigations may be difficult due to differences in experimental techniques.…”
Section: Discussionsupporting
confidence: 57%
“…This finding was also supported by in vitro experiments showing that epithelial cells of the lung, alveolar macrophages and brain tissues are permissive for FeMV-2 under laboratory conditions [24,37]. On the other hand, in a recently detected infection of black leopards (Panthera pardus) with FeMV-1, only kidneys were affected [38]. Further studies addressing surveillance of paramyxoviruses in wildlife animals should take into account that organs other than the kidney may also be a target of viral replication and should therefore be sampled to elucidate the complete tissue tropism of these viruses.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…To confirm the concordant results of viral-like particles by TEM and FeMV nucleic acid detected by RT-qPCR, the kidney sections of both cats were subjected to immunohistochemistry (IHC) to determine the presence of FeMV antigen using Pab-His-rFeMV-M. 10,12 Prominent FeMV immunoreactivity was localized in renal tubular epithelial cells, where the eosinophilic, intracytoplasmic, hyalinized globular materials were found (Fig. 4, inset).…”
mentioning
confidence: 87%
“…The FeMV‐1 genotype is closely related to the first FeMV strain identified in China and can infect kidney tissues. Although this genotype was associated with tubulointerstitial nephritis (TIN) and chronic kidney disease (CKD) in domestic cats and wild cats (Nambulli et al., 2016; Piewbang et al., 2020; Sutummaporn et al., 2019), it was also detected in cats without renal diseases (Darold et al., 2017). Meanwhile, the FeMV‐2, first detected in Germany, is known to infect a wide variety of tissues other than renal cells, including pulmonary and cerebral tissues (Sieg et al., 2019).…”
Section: Introductionmentioning
confidence: 99%